2022
DOI: 10.1039/d2cc00361a
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal ion binding using cyclic polyketones

Abstract: Cyclic oligoketones composed of 3,3-dimethylpentane-2,4-diones showed crown ether-like alkali metal ion binding behavoir with association constants up to 1.7 x 104 M–1 in chloroform/acetonitrile (v/v, 9/1). The binding properties have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Second, polyketone forms coordinated bonds (with the ZnO surface) with its carbonyl groups facing the ZnO surface, as well as coordinated bonds with the hydrocarbon substituent facing the outside, resulting in a more lipophilic surface that enhances affinity and coexistence with biological materials. Third, polyketone is structurally flexible, and previous studies have shown that it has a high affinity for metal ions ( 46 ), adsorbing efficiently on surfaces with many irregularities, such as metal oxides, by adopting a stable adsorption structure. Fourth, although the polyketones used in this study are artificial compounds, they share chemical structural similarity with the precursors of polyketide metabolites commonly found in biosynthetic systems; thus, polyketones should be compatible with lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Second, polyketone forms coordinated bonds (with the ZnO surface) with its carbonyl groups facing the ZnO surface, as well as coordinated bonds with the hydrocarbon substituent facing the outside, resulting in a more lipophilic surface that enhances affinity and coexistence with biological materials. Third, polyketone is structurally flexible, and previous studies have shown that it has a high affinity for metal ions ( 46 ), adsorbing efficiently on surfaces with many irregularities, such as metal oxides, by adopting a stable adsorption structure. Fourth, although the polyketones used in this study are artificial compounds, they share chemical structural similarity with the precursors of polyketide metabolites commonly found in biosynthetic systems; thus, polyketones should be compatible with lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…To realize the ring tightening synthesis of calix [3]pyrrole, our group has developed stepwise oligomerization 76,77 and macrocyclization 78 Calix [3]pyrrole 60 was rst synthesized in 41% yield through a triple Paal-Knorr reaction using cyclic hexaketone 59 and ammonium acetate (Scheme 9). An important factor in the successful synthesis of 60 is the use of non-acidic reaction conditions because acids commonly used under Rothemund-Lindsey conditions, such as TFA, trigger rapid, quantitative strain-induced ring expansion of 60, which will be discussed in Section 3.…”
Section: Ring Tightening Approachmentioning
confidence: 99%
“…[2][3][4][5] Chemistry driven by the size-specific capture of group-IA and -IIA metal cations with crown ethers was soon expanded, spurring decades of advancements in host-guest and supramolecular chemistry harnessing more general non-covalent interactions. The incorporation of multiple oxygen atoms is a key structural feature for designing cation-trapping macrocycles, e.g., sophisticated cage-like cryptands, [6][7][8][9][10][11] calix[n]arenes with phenols, [12][13][14][15][16][17][18] Kläui oxygen tripodal ligands, [19][20][21][22] polyorganostannates, 23,24 tris(methoxysilyl)crystallogenides, 25,26 and cyclic peptides, 13,[27][28][29] as well as recently developed polyketones [30][31][32] featuring multiple carbonyl oxygen atoms. In addition to oxygen-based macrocycles, nitrogen counterparts such as porphyrins have emerged in nature that accommodate a variety of transition metals to significantly expand the scope of vital biocatalytic transformations.…”
Section: Introductionmentioning
confidence: 99%